The impact of ECB monetary policy decisions and communication on the yield curve - Claus Brand; Daniel Buncic; Jarkko Turunen (European Central Bank (ECB), 2006)
We analyse high-frequency changes in the euro area money market yield curve on dates when the ECB regularly sets and communicates decisions on policy interest rates to construct different indicators of monetary policy news relating to policy decisions and to central bank communication. The indicators show that ECB communication during the press conference may result in significant changes in market expectations of the path of monetary policy. Furthermore, our results suggest that these changes have a significant and sizeable impact on medium to long-term interest rates.
Keywords: E43; E58; 330; central bank communication; ECB; Money market rates; yield curve; Zentralbank; Öffentlichkeitsarbeit; Geldpolitik; Erwartungsbildung; Zinsstruktur; EU-Staaten